Variaciones en la diversidad de la comunidad bentónica del sedimento. Un indicador biológico del estado de contaminación de los ríos de la subregión de Heredia, Costa Rica. - Charpentier, Claudia (1988)
Between September 1985 and February 1987, 8 rivers located in the Central region of the Province of Heredia were sampled. A total of 26 stations were located for the study, with sampling intervals of 60   to 90 days. In each station there sediment samples were taken to determine the benthic community, The  data obtaines were analized using the Sequential Comparation Index (SCI) of Cairns and Dickson (1971), and the resulting data were further analized with a multivariable analysis to determinate changes in the community in time and space for all the rivers studied and for each one individually. The rivers Segundo, Tibás and Porrosatí showed high SCI values, and these result in combination with the microbiological and physico-chemical data, let us list them as short-term recuperation lotic systems. Rivers Bermudez and Quebrada Seca showed low SCI values, with very little recuperation signs during the rainy season, and therefore were classified as polluted and with a much slower recuperation capacity. Rivers Burío, Pirro and Porrosatí were catalogued as heavily polluted and the recuperation possibilities are in a very long term.